Poverty, empowerment and social development in the Caribbean - Girvan, Norman ed. (Canoe P. MonaJM, 1997)
Addresses five themes, viz. the interrelationship between social and economic development; the generation of productive employment; the alleviation and reduction of poverty; and, the role of government, the private sector and NGOs in social development.